Post mastectomy pain control using bupivacaine installation via wound drains - Alhussini, Mahmoud A.; Awad, Ahmed T.; Girgis, Akram M.; El Fayomi, Tarek A.; Agameya, H. M. (International Surgery Journal, 2019)
Background: This study is a controlled prospective randomized blinded study. Our aim was to evaluate the effect of wound installation with bupivacanie through surgical drains to control postoperative pain and decrease the use of systemic analgesics after mastectomy. Methods: This study was conducted on 168 female patients candidates for modified radical mastectomy admitted to the Surgical Oncology Unit, Faculty of Medicine, University of Alexandria. Patients were randomly divided into two equal groups. Group A Bupivacaine was installed through axillary and chest wall drains by the end of surgery. While, group B was installed by equal amount of normal saline as placebo. We assessed the visual analogue score (VAS), need and timing for systemic analgesics during the first 24 hours. Results: The mean values for VAS were always lower in group A. This was reflected on the timing and need for additional analgesia. Conclusions: We concluded from this study that using bupivacaine instillation through surgical drains is an effective and easy method to control post mastectomy pain and enhance patients' recovery in the first 24 hours postoperative.